Copper film deposition using a helium dielectric barrier discharge jet. Issue 11 (15th June 2020) - Tsai, Tsung‐Chan; Mcintyre, Katelyn; Burnette, Matthew; Staack, David
Abstract: This study demonstrates that plasma‐enhanced chemical vapor deposition of copper films can be achieved in ambient air and at low temperature. A helium dielectric barrier discharge jet with a small mixture of hydrogen and copper(II) acetylacetonate vapor is utilized as the nonthermal plasma source to deposit conductive copper films with low electrical resistivity (<1 × 10 −7 Ω·m). The deposited film appears to have three distinct regions (reddish brown, dark blue, and yellowish) from center to edge. Copper nanograins ( 50 nm) are observed in both the reddish‐brown and the dark‐blue regions, whereas the yellowish region exhibits a continuous structure containing copper oxide. The copper films are further deposited on various temperature‐sensitive substrates, including plastic, cardboard, agar, and pork skin. Abstract : Plasma‐enhanced chemical vapor deposition of copper films is achieved in ambient air and at low temperature using a helium dielectric barrier discharge jet. The deposited copper films are characterized. Film deposition is also achievable on temperature‐sensitive substrates, such as plastic, cardboard, agar, and pork skin.